Use of Microalgae for the Control of Luminous Vibriosis in Tropical Shrimp Aquaculture: Luminous Vibriosis Control by Microalgae - A. Caipang, Christopher Marlowe; N. Aguana, Mary Paz (Biological Sciences - PJSIR, 2014)